Cestrum lozadai (Solanaceae), a new species from the state of Guerrero, Mexico - Cruz Durán, Ramiro; Valencia-A., Susana (Phytotaxa, 2022)
A new species from the cloud forest in the state of Guerrero, Mexico, is described and illustrated: Cestrum lozadai. This new entity is similar to C. laxum; however, it is distinguished from the latter by presenting narrower leaf blades, with up to 15 pairs of secondary veins, flowers with longer pedicels, up to 16 mm and articulated, the corolla tube longer, up to 21 mm and internally with retrorse trichomes in the portion attached to the filaments, with the fused part of the filaments up to 15 mm, and with a known distribution only in the state of Guerrero, Mexico.